Pengalaman Menggunakan Terapi Komplementer pada Pasien Kanker Payudara - Stevani Basry; Kusman Ibrahim; Ida Maryati (Jurnal Keperawatan Silampari, 2022)
This study aims to obtain information related to the experiences of breast cancer patients using complementary therapies at Adventist Hospital in Bandung City. This research method is qualitative research with a descriptive explorative research type. The results of this study provide an overview of breast cancer patients' experiences using complementary therapies. This experience is described in six themes, namely: (1) herbal is the leading choice of complementary therapy; (2) friends are a source of information in determining the type of complementary therapy; (3) complementary therapy requires a lengthy healing time; (4) fear of surgery is the main reason for choosing complementary therapy; (5) expensive cost is an obstacle that is often encountered in using complementary therapy; (6) the use of CAM as an effort to improve the welfare of breast cancer patients. In conclusion, complementary therapies such as good herbal medicine, juice therapy, electro-capacitive cancer therapy (ECCT), gamat jelly, and Papuan ant nest teas have varying prices. When used for a long time, the accumulated costs incurred are more expensive than operating costs. . Keywords: Breast Cancer, Experience, Complementary Therapy